Distinct associations of computer/mobile devices use and TV watching with depressive symptoms in adults: A large population study in China. Issue 9 (3rd July 2019) - Yu, Bin; Gu, Yeqing; Bao, Xue; Meng, Ge; Wu, Hongmei; Zhang, Qing; Liu, Li; Sun, Shaomei; Wang, Xing; Zhou, Ming; Jia, Qiyu; Song, Kun; et al.
Abstract: Background: Recent evidence shows that screen time may be an important risk factor for mental health. The aim of this study was to examine the association of computer/mobile devices (CMD) use and TV watching separately with depressive symptoms in a large representative sample of Chinese adults. Methods: A sample of 18, 994 adults in Tianjin, China was studied in a cross‐sectional analysis. Depressive symptoms were assessed using the Self‐Rating Depression Scale (SDS). CMD use and TV watching time were self‐reported and divided into five categories. The associations were estimated by odds ratios (ORs) using logistic regression models adjusted for multiple confounders. Results: The prevalence of elevated depressive symptoms was 16.3% (SDS ≥ 45). For CMD use, the ORs of the depressive symptoms decreased across time levels. Compared with the least use time (<1 hr/day), multivariable‐adjusted ORs (95% confidence interval [CI]) of other time categories for elevated depressive symptoms were 0.78 (0.66, 0.91), 0.67 (0.57, 0.80), 0.65 (0.54, 0.77), and 0.77 (0.62, 0.96) respectively. For TV watching, the ORs of the depressive symptoms increased across time levels. Compared with the least watching time (<1 hr/day), multivariable‐adjusted ORs (95% CI) for elevated depressive symptoms across the time categories were 1.00 (0.89, 1.12), 1.28 (1.11, 1.48), 1.26 (0.98, 1.60), and 1.95 (1.10, 3.35), respectively. Conclusions: These findings suggested that different types of screen time may play different roles in the mental health of general adults. Further studies are needed to clarify the reasons for these distinct associations.